How much time do internal medicine residents spend on self-directed learning and on which resources: a multi-center study - Trivedi, Shreya P.; Artino, Anthony R.; Rodman, Adam; Jones, R. Logan; Al-Mondhiry, Jafar; Rowe, Timothy; Larsen, Tyler; Ambert-Pompey, Sarai; Rai, Devesh; Ghoneem, Ahmed; Gowen, Nicholas; Manolas, Melina; et al. (Medical education online, 2025)
Increased clinical demands and newer means of self-directed learning (SDL) necessitate an understanding of how medical residents are supporting their learning. To examine the patterns of SDL engagement among internal medicine residents, their attitudes and behaviors with various resources, and evaluate the relationship between the clinical learning environment (CLE) and the time residents allocate to SDL and types of resources. This cross-sectional study used a systematic questionnaire informed by previous qualitative research on SDL among internal medicine residents. Internal medicine (IM) residents from 10 residency programs across the United States participated, providing a diverse representation of geographical and institutional contexts. Residents were asked to estimate weekly hours spent on SDL during their last clinical rotation, on which resources, and then to rank the usefulness of each resource. The survey also measured several variables, including attitudes and behaviors after using the resource they perceived to be the most useful, and the influence of training level, residency program type, clinical rotation, and number of hours worked clinically per week on reported time spent on SDL and types of resources. The response rate was 69.5% (783/1,126). Residents dedicated a mean of 18.2 (SD 18.6) hours per week (median of 10.5 hours per week) to SDL. Community-based programs reported more hours of SDL. There was no difference in hours spent on SDL based on the last clinical rotation, number of hours worked clinically, or PGY level. Senior residents favored digital resources, like podcasts, and were less likely to use traditional resources, like textbooks than interns. Our findings underscore the substantial time residents devote to SDL. In light of these results, educators and healthcare systems will need to work together to better support residents in optimizing the complex clinical learning environment.